Descendants. Stories from Auradon and beyond - Behling, Steve (Los Angeles : Disney Press, 2024)
Contains four stories about the magical world of Auradon, where the children of Disney princes and princesses live, and the Isle of the Lost, where the children of Disney villains live, and how these children meet each other at Auradon Prep.
Descendants. Welcome to Auradon -- Descendants 2. Back to the Isle -- Descendants 3. Stronger together -- Descendants, the rise of Red. Paint this town red.
"A 4-in-1 reader"--Front cover.
K-3
610L
Keywords: Teenage girls -- Juvenile fiction; Preparatory schools -- Juvenile fiction; Disney characters -- Juvenile fiction; Magic -- Juvenile fiction; Teenage girls -- Fiction; Preparatory schools -- Fiction; Disney characters -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction; Adaptations; Readers (Elementary)